Determinants of knowledge sharing at Royal Malaysian Customs Johor Bahru / Azrul Hadi Abu Zahrin - Abu Zahrin, Azrul Hadi (Faculty of Business Management, 2016)
This research was conducted to carry out a study entitled “Determinants of Knowledge Sharing at Royal Malaysian Customs Johor Bahru (RMCJB)”. The purpose is actually to study on the relationship between three independent variables against one dependent variable. Basically, it consists of three factors influencing knowledge sharing among employees at RMCJB and the factors include motivator factors (community-related consideration, personal benefit, and normative consideration), enabler factors (organizational climate, trust and social capital) and barrier factors (organizational climate and organizational structure). The study reported is based on the questionnaire circulated to employees at Royal Malaysian Customs Johor Bahru which is at Menara Kastam and Bangunan Sultan Iskandar (BSI). In order to complete this thesis, a few hypotheses were constructed and focused on the objectives to determine whether there were significant relationships between the variables. For this study, 226 employees working at Royal Malaysian Customs Johor Bahru were chosen as respondents. The data was obtained from primary data by using questionnaire. All data collected through questionnaire were analyzed systematically by using Statistical Package for Social Science (SPSS).